2011
DOI: 10.1099/mic.0.045740-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel σ B regulation modules of Gram-positive bacteria involve the use of complex hybrid histidine kinases

Abstract: A common bacterial strategy to cope with stressful conditions is the activation of alternative sigma factors that control specific regulons enabling targeted responses. In the human pathogen Bacillus cereus, activation of the major stress-responsive sigma factor s B is controlled by a signalling route that involves the multi-sensor hybrid histidine kinase RsbK. RsbK-type kinases are not restricted to the B. cereus group, but occur in a wide variety of other bacterial species, including members of the the low-G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 48 publications
1
50
0
Order By: Relevance
“…In B. subtilis , σ B activity is controlled by RsbVW partner-switching, a mechanism which is highly conserved in species that contain σ B , including B. cereus strains (de Been et al, 2010, 2011). In non-stressed cells, σ B is present in an inactive form by complexation with the anti-sigma factor RsbW.…”
Section: General Stress Responsementioning
confidence: 99%
See 3 more Smart Citations
“…In B. subtilis , σ B activity is controlled by RsbVW partner-switching, a mechanism which is highly conserved in species that contain σ B , including B. cereus strains (de Been et al, 2010, 2011). In non-stressed cells, σ B is present in an inactive form by complexation with the anti-sigma factor RsbW.…”
Section: General Stress Responsementioning
confidence: 99%
“…In the human pathogen B. cereus , the mechanism of σ B activation has only been studied more recently (van Schaik et al, 2004a,b, 2005, 2007; de Been et al, 2010, 2011). It has been shown that σ B activation is governed by a single PP2C-type phosphatase, RsbY, which carries an N-terminal response receiver (REC) domain (van Schaik et al, 2005).…”
Section: General Stress Responsementioning
confidence: 99%
See 2 more Smart Citations
“…Partner-switching systems are one among other mechanisms by which bacteria connect cue transmission and gene expression (27)(28)(29). The partner-switching system that regulates B consists of an antisigma factor with a kinase activity (RsbW), two phosphatases (RsbU and RsbP), and an anti-sigma antagonist (RsbV) that contains a phosphorylatable serine residue in its sequence.…”
mentioning
confidence: 99%